Unveil the complexity of the molecular machinery involved in erythrophagocytosis by macrophages - Santarino, Inês Barreira (2020)
ABSTRACT: Erythrophagocytosis is a highly regulated process where sequential events ensure the proper internalization and clearance of red blood cells. However, details on these processes are scarce and not fully understood, making it difficult to modulate and possibly treat associated diseases, such as malaria and sickle-cell disease. After their development in the bone marrow, red blood cells have a life span of approximately 120 days. With time, the plasma membrane of red blood cells undergoes deleterious changes that make the cell susceptible to clearance by macrophages – a process known as senescence. Before this process, erythrocytes may undergo cell death – eryptosis - a similar process that occurs in nucleated cells. In both cases, clearance must occur efficiently in order to avoid the accumulation of free hemoglobin and heme and maintain the iron levels required for homeostasis. Processing of red blood cells by macrophages implies the interaction of nascent phagosomes with endocytic compartments until fusion with lysosomes where component degradation takes place –phagolysosome biogenesis. In the first part of this dissertation, this process was assessed in mouse macrophages from two different sources: bone marrow and the peritoneal cavity. As phagocytic particles involved in erythrophagocytosis, we generated three types of red blood cell models: 1) senescent/eryptotic red blood cells (aged red blood cells) from human blood, and opsonized-red blood cells from sheep blood, 2) IgG- and 3) complement-opsonized. After assessing the acquisition of early and late markers of phagolysosome biogenesis, we concluded that aged red blood cells containing phagosomes mature slower compared to opsonized targets and therefore reach the lysosomes with a delay. As aged red blood cells are the best suited model to mimic senescence/eryptosis due to the exposure of phosphatidylserine on the surface, another aim of this dissertation was to identify other molecular partners in the process of phagolysosome biogenesis. We have found, for the first time, that erythrophagocytosis is LAP-mediated, that is, it involves the recruitment of LC3. Additionally, we identified other proteins from the autophagy machinery such as p62, NBR1 and NDP52, and their association to phagosomes is dependent on ubiquitin. They exhibit different association hierarchies with phagosomal membranes and comparing differences between aged and IgG-Opsonized red blood cells, the most striking outcome was obtained for p62. This autophagy effector exhibited selectivity for aged RBC-containing phagosomal membranes and, surprisingly, it is crucial for their degradation. Interestingly, phosphorylation of p62 on its Ser351 residue after erythrophagocytosis activates the non-canonical NRF2-signalling pathway, inducing the translocation of this transcription factor to the nucleus where p62, Hmox1 and Sod2 genes are up-regulated, contributing to the maintenance of cell homeostasis. In the absence of NRF2, degradation of red blood cells is also impaired. These outcomes imply a positive feedback loop between p62 and NRF2 in promoting efficient red blood cell clearance. Therefore, our findings contributed to unravelling the molecular mechanisms underlying phagolysosome biogenesis in erythrophagocytosis, opening new avenues to understand the severity of hemolytic diseases and possibly modulate the process.